Growth responses of Populus tremuloides clones to interacting elevated carbon dioxide and tropospheric ozone - Isebrands, J.G; McDonald, E.P; Kruger, E; Hendrey, G; Percy, K; Pregitzer, K; Sober, J; Karnosky, D.F (Environmental pollution (1987), 2001)
Elevated ozone negates expected positive growth effects of elevated CO 2 in Populus tremuloides in the field. The Intergovernmental Panel of Climate Change (IPCC) has concluded that the greenhouse gases carbon dioxide (CO 2) and tropospheric ozone (O 3) are increasing concomitantly globally. Little is known about the effect of these interacting gases on growth, survival, and productivity of forest ecosystems. In this study we assess the effects of three successive years of exposure to combinations of elevated CO 2 and O 3 on growth responses in a five trembling aspen ( Populus tremuloides) clonal mixture in a regenerating stand. The experiment is located in Rhinelander, Wisconsin, USA (45°N 89°W) and employs free air carbon dioxide and ozone enrichment (FACE) technology. The aspen stand was exposed to a factorial combination of four treatments consisting of elevated CO 2 (560 ppm), elevated O 3 (episodic exposure-90 μ1 1 −1 hour −1), a combination of elevated CO 2 and O 3, and ambient control in 30 m treatment rings with three replications. Our overall results showed that our three growth parameters including height, diameter and volume were increased by elevated CO 2, decreased by elevated O 3, and were not significantly different from the ambient control under elevated CO 2+O 3. However, there were significant clonal differences in the responses; all five clones exhibited increased growth with elevated CO 2, one clone showed an increase with elevated O 3, and two clones showed an increase over the control with elevated CO 2+O 3, two clones showed a decrease, and one was not significantly different from the control. Notably, there was a significant increase in current terminal shoot dieback with elevated CO 2 during the 1999–2000 dormant season. Dieback was especially prominent in two of the five clones, and was attributed to those clones growing longer into the autumnal season where they were subject to frost. Our results show that elevated O 3 negates expected positive growth effects of elevated CO 2 in Populus tremuloides in the field, and suggest that future climate model predictions should take into account the offsetting effects of elevated O 3 on CO 2 enrichment when estimating future growth of trembling aspen stands.